WhaleBot Alerts Telegram Channel and Google Alerts as Information Media for XRP Cryptocurrency Traders - Lady Joanne Tjahyana (Master of Management, School of Business and Management, Petra Christian University, 2024)
Ripple (XRP) is one of the most significant cryptocurrencies that attracts many traders to invest. Traders often look for information from the media as a reference for their trading management strategy. This research aims to utilize WhaleBot Alerts Telegram channel and Google Alerts as trading information media by looking for the relationship between whale transactions, news sentiment, and price returns. The researcher collected XRP whale transactions from the WhaleBot Alerts Telegram channel and XRP news from Google Alerts within a crypto winter period, from November 2021 to January 2023, and analyzed the data using descriptive statistical analysis. This research also follows several variables and formulas from previous studies. After analyzing 457 XRP whale transaction datasets, the researcher finds a significant relationship between the number of trading days and trading return on investment. The relationship shows that the more days, the greater the chance of profit. The other variables give reference patterns, such as the number of whale transactions, total whale transaction value, the most significant transaction value, and news topic. Finally, this research develops a simple XRP short-term trading model using the WhaleBot Alerts Telegram channel data and Google Alerts. In conclusion, trading initiated by XRP whale's transactions and XRP news could give a 76.53% chance of making a profit. Therefore, XRP traders can use the WhaleBot Alerts Telegram channel and Google Alerts as their trading information media.